TEKNIK PENILAIAN BERBASIS KELAS DAN KONSEP DIRI DALAM PEMBELAJARAN BIOLOGI - Siti Nurasiah (Jurnal Evaluasi Pendidikan, 2016)
This study was conducted in SMAN 1 Cilamaya Karawang. The samples were 80 students of 11th grade of Science Major in the second semester of the 2015/2016 academic year. Samples were selected by using simple random sampling technique. The research method adopted was the experimental method. While the study design is the treatment by level 2x2 design. The data collection was done by measuring the academic self concept of students and students’biology learning outcomes. The hypothesis was tested by using analysis of variance (ANOVA). The research result has a positive impact on improving the evaluation system of learning in high school as well as improvement in student’s biology learning outcomes.